Pengaruh Konsentrasi Tepung Rumput Laut Caulerpa Sp Dalam Pakan Buatan Terhadap Pertumbuhan Ikan Bandeng (Chanos Chanos) - Magfiratun Magfiratun; Rahmi Rahmi; Nur Insana Salam; Syawaluddin Soadiq; Andi Chadijah (Samakia : Jurnal Ilmu Perikanan, 2024)
Caulerpa sp is a group of green algae, thallus (branches) in the form of sheets, rods and spheres, soft to hard and siphonous structure. Caulerpa is one of the seaweed commodities that has been used by the community directly as food in the form of fresh vegetables and vegetables. Caulerpa sp has a fairly high nutritional content, including 0.77% fat, 5.99% protein, 4.12% water, 60.54% ash, 16% crude fiber. These nutrients can be used as raw materials in the manufacture of feed. This study aims to determine the effect of the concentration of Caulerpa sp flour in artificial feed on the growth of milkfish (Chanos chanos). The experimental design in this study was a completely randomized design (CRD) with 4 treatments, namely: A. 10% Caulerpa sp, B. 15% Caulerpa sp, C. 20% Caulerpa sp, and D (Control). each treatment was tested with 3 replications. The results of this study indicate that the addition of caulerpa sp flour with a concentration of 20% (C) can provide the best growth of 2.20 grams of milkfish